Syphilis at the crossroad of phylogenetics and paleopathology. - Fernando Lucas de Melo; Joana Carvalho Moreira de Mello; Ana Maria Fraga; Kelly Nunes; Sabine Eggers (Public Library of Science (PLoS), 2010)
The origin of syphilis is still controversial. Different research avenues explore its fascinating history. Here we employed a new integrative approach, where paleopathology and molecular analyses are combined. As an exercise to test the validity of this approach we examined different hypotheses on the origin of syphilis and other human diseases caused by treponemes (treponematoses). Initially, we constructed a worldwide map containing all accessible reports on palaeopathological evidences of treponematoses before Columbus's return to Europe. Then, we selected the oldest ones to calibrate the time of the most recent common ancestor of Treponema pallidum subsp. pallidum, T. pallidum subsp. endemicum and T. pallidum subsp. pertenue in phylogenetic analyses with 21 genetic regions of different T. pallidum strains previously reported. Finally, we estimated the treponemes' evolutionary rate to test three scenarios: A) if treponematoses accompanied human evolution since Homo erectus; B) if venereal syphilis arose very recently from less virulent strains caught in the New World about 500 years ago, and C) if it emerged in the Americas between 16,500 and 5,000 years ago. Two of the resulting evolutionary rates were unlikely and do not explain the existent osseous evidence. Thus, treponematoses, as we know them today, did not emerge with H. erectus, nor did venereal syphilis appear only five centuries ago. However, considering 16,500 years before present (yBP) as the time of the first colonization of the Americas, and approximately 5,000 yBP as the oldest probable evidence of venereal syphilis in the world, we could not entirely reject hypothesis C. We confirm that syphilis seems to have emerged in this time span, since the resulting evolutionary rate is compatible with those observed in other bacteria. In contrast, if the claims of precolumbian venereal syphilis outside the Americas are taken into account, the place of origin remains unsolved. Finally, the endeavor of joining paleopathology and phylogenetics proved to be a fruitful and promising approach for the study of infectious diseases.